Data availability on Nutrition Sensitive Social Protection Programs (NSSPPs) across population-based surveys in South Asia - Neupane, Sumanta; Scott, Samuel P.; Jangid, Manita; Shapleigh, Sara; Kim, Sunny S.; Akseer, Nadia; Heidkamp, Rebecca A.; Menon, Purnima (International Food Policy Research Institute, 2022)
Social safety nets (SSN) are cash or in-kind/food transfer programs designed to help individuals and households cope with chronic poverty, destitution, and vulnerability (World Bank, 2018). Some of these social protection programs include conditions or additional interventions that can enhance their impact on nutrition. Examples include attending health and nutrition services, targeting households with nutritionally vulnerable members (e.g., pregnant, and lactating women, children under 24 months), administration of transfers in a ender-sensitive manner, distributing transfers during periods of seasonal or climatic vulnerability, and focusing on emergencies (Ruel & Alderman, 2013; Alderman, 2016) developed a framework that identifies which of the World Bank ASPIRE categories of social safety nets have the potential to be nutrition sensitive. These are captured in six broad categories with multiple program subcategories (Table 1).